Detection of malaria in Malaysia by nested polymerase chain reaction amplification of dried blood spots on filter papers - Balbir, Singh; Janet, Cox-Singh; Andy Oliver, Miller; Mohammad Syukri, Abdullah; Georges, Snounou; Hassan, Rahman Abdul (Transactions of the Royal Society of Tropical Medicine and Hygiene, 1996)
Balbir Singh, Janet Cox-Singh, Andy Olivier Miller, Mohammad Shukri Abdullah, Georges Snounou, Hasan Abdul Rahman,